Achieving real-time guarantees in mobile wireless ad hoc networks. - CAHILL, VINNY (IEEE, 2003)
Timely wireless communication is essential to allow real-time mobile applications, such as communication between mobile robots or inter-vehicle communication to be realized. The real-time event-based communication paradigm has been recognized as an appropriate highlevel communication scheme to connect autonomous components in large distributed control systems [1]. We investigate whether real-time event constraints can be guaranteed in a mobile ad hoc wireless network. In this work in progress paper we present our analysis of the impact of mobile ad hoc wireless networks on achieving real-time guarantees. We introduce our ongoing work on the use of a proactive routing and resource reservation protocol using mobility awareness and prediction to reduce the unpredictability of a dynamic mobile ad hoc wireless network.
Proceedings of the 24th IEEE Real-Time Systems Symposium Work-in-progress Session (RTSS '03)
24th IEEE Real-Time Systems Symposium Work-in-progress Session (RTSS '03)
PUBLISHED
Keywords: Computer Science